Natação Adaptada: análise da função pulmonar de pessoas com deficiência - Dias, Natalia Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The research discusses the pulmonary function of the students of SORRI that are part of the Project for the extension of the Department of Physical Education in Bauru Swimming for People with Disabilities during the aquatic activities, noting the changes in efficiency class of breathing with the practice of aquatic activity, by the analysis of the volume and respiratory capacity. The respiratory control is essential in the process of adaptation to the liquid medium, because a student who fails to immerse the face in the water will not be able to adopt a horizontal position sufficiently stable. The practice of aquatic activities requires a great effort of breathing. Therefore, the practice of aquatic activities influence favorably the breathing, because the movements performed in the water tone the diaphragm, which is the essential muscle of the breathing, allowing an improvement in pulmonary ventilation. For the purposes of this study, the sample was composed of 10 students of the SORRI of the city of Bauru forming part of the project Swimming for People with Disabilities, practicing swimming once a week for 1 hour. For the collection of lung volumes and capacities was used a transducer of air flow and a unit of data collection, model MP36, both of the brand Biopac connected to a computer, where the data were collected and recorded for later analysis. Two tests were carried out in a day with each participant in the project of swimming, and a test at the beginning of the lesson, at rest, and another after a series of 10 breaths carried out within the swimming pool. These tests were performed in the months of March and April. The analysis of the data was through the medium of the figures and also individually, noting the changes in respiratory function of students practicing aquatic activities, without which there would be no comparison between the participants. The measurements of the scores on the pre- and post-exercise show that the...

O trabalho tem como proposta analisar a função pulmonar dos alunos da SORRI que fazem parte do Projeto de Extensão do Departamento de Educação Física de Bauru Natação para Pessoas com Deficiência durante as atividades aquáticas, verificando as alterações na eficiência da respiração com a prática da atividade aquática, pela da análise dos volumes e capacidades respiratórias. O controle respiratório é fundamental no processo de adaptação ao meio líquido, pois um aluno que não consegue imergir o rosto na água não irá conseguir adotar uma posição horizontal suficientemente estável. A prática de atividades aquáticas exige um grande esforço da respiração. Portanto, a prática de atividades aquáticas influencia beneficamente a respiração, já que os movimentos executados dentro de água tonificam o diafragma, que é o músculo essencial da respiração, permitindo uma melhora na ventilação pulmonar. Para realização deste estudo, a amostra foi composta por 10 alunos da SORRI da cidade de Bauru que fazem parte do projeto Natação para Pessoas com Deficiência, praticando natação uma vez por semana durante 1 hora. Para a coleta dos volumes e capacidades pulmonares foi utilizado um transdutor de fluxo aéreo e uma unidade de coleta de dados, modelo MP36, ambos da marca Biopac conectado a um computador, onde os dados foram coletados e gravados para análise posterior. Foram realizados dois testes em um dia com cada participante do projeto de natação, sendo um teste no início da aula, em repouso, e outro após uma série de 10 respirações realizadas dentro da piscina. Estes testes foram realizados nos meses de março e abril. A análise dos dados foi através da média dos valores apresentados e também de maneira individual, verificando as alterações na função respiratória dos alunos praticantes de atividades aquáticas, sem que houvesse comparação entre os participantes. As...
Keywords: Esportes para deficientes; Respiração - Medição; Esportes aquaticos; Insuficiencia respiratoria; Sports for the handicapped